A Note on the Equipment and Machinery for Democracy in Classical Athens: A Rhetorical Perspective on Material Evidence - Enos, Richard Leo (Journal of technical writing and communication, 2025)
The relationship between democracy and literacy is a longstanding topic of interest both to contemporary communication scholars as well as historians of rhetoric. Democracy and literacy are both social activities. Focusing on the Classical Period of Athens (ca. 480–323 BCE) as a specific site of study, this essay argues that the dynamic interaction of these two activities was facilitated by the development and application of technological equipment. That is, technology, in this case, refers to the equipment and machinery ancient Athenians utilized that enhanced their literate skills in order to facilitate the performance of democratic activities. Archaeological excavations over the last century, especially at the Agora, have yielded artifacts that provide evidence of the technological implements used in democratic activities. This study offers an analysis of recently excavated artifacts arguing that Athenians developed and employed equipment that utilized literacy in order to enhance the civic processes of democracy. This field study advances the conclusion that the relationship between democracy and literacy in classical Athens requires an understanding of a third factor: the impact of technology.